SOME FIXED POINT RESULTS FOR UNIFORMLY QUASI-LIPSCHITZIAN MAPPINGS IN CONVEX METRIC SPACES - Yildirim, I.; Khan, S. H.; Ozdemir, M. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2012)
In this paper, an iteration process for approximating common fixed points of two uniformly quasi Lipschitzian mappings in convex metric spaces is defined. Without using "the rate of convergence condition" _n=1^∞(k_n-1)<∞ associated with asymptotically (quasi-)nonexpansive mappings. some convergence theorems are also proved. The results presented generalize, improve and unify some recent results.